Characteristics of irrigation tube wells on major river flood plains in Bauchi State, Nigeria - Abubakar Sadiq, Abdullahi; Abubakar Amin, Sunusi; Ahmad, Desa; Umara, Baba Gana (Institute for Environmental Research in Hydrographic Basins, University of Taubaté, 2014)
Water for traditional irrigation on flood-plains in Bauchi State is obtained from the Jama’are, Gongola and Komadugu river systems. The plains are replenished during rainy season and farmers often drill wells to irrigate their farm lands. Wells are drilled by jetting techniques and most of the farmers’ plots are less than 1 hectare. Well yield varies from 0.6 to 9.4 Ls-1 and water is drawn from a depth of 12 m. From the mean yield, the results indicate higher water abstraction from tube wells located at Jama’are flood plains. The study recommended appropriately locating wells and greater investment in extension services in order to facilitate the growth of farmer associations.